HYPOGLYCEMIA ASSESSMENT AMONG TYPE 2 PATIENTS WITH DIABETES RECEIVING INSULIN BASALOG AND INSULIN LANTUS: A CROSSOVER RANDOMIZED CONTROLLED TRIAL USING CONTINUOUS GLUCOSE MONITORING SYSTEM (CGMS) - Adam, Ida Ilyani; Mustafa, Norlaila; Wahab, Norasyikin Abdul; Ibrahim, Nor Akhmar; Deligannu, Pravina (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Hypoglycemia is a major limiting factor among insulin-treated patients in achieving optimal glycemic control. Analose and biosimilar insulins have been shown to produce reductions in the hypoglycemia rates, however the actual assessment of hypoglycemia comparing insulin Lantus and the biosimilar insulin Basalog has not been described before. OBJECTIVE To evaluate hypoglycemia rates amongst T2DM patients receiving Basalog vs Lantus using continuous glucose monitoring (CGM). METHODOLOGY A single centre, randomized, open-label, crossover study was conducted over a 12-week period among T2DM patients (n=55), randomised into two-arm parallel group; Basalog and Lantus. Hypoglycemia was described by evaluating Low Blood Glucose Index (LBGI), M-value and Standard Deviation (SD) from CGM. Independent and paired sample t-test and one-way ANCOVA was performed using SPSS. RESULTS The respondents in Basalog (n=27) and Lantus (n=28) arm were similar in socio-demographics, duration of DM, complications of DM, comorbidities, use of oral hypoglycaemic agents, antihypertensive medications and lipid lowering drugs (p>0.05). No difference in anthropometrics, vital signs, lipid profile, renal profile, full blood count, liver function and urine microalbumin was found between the groups (p>0.05). Mean HbA1c was 8.8% and 8.7% with Glargine and Basalog, at baseline respectively. Both insulins had no significant differences in SD (2.7±0.99 vs 2.5±0.93, p>0.05) and M value (15.9±18.11 vs 14.9±25.01, p>0.05). There was lesser low CGM excursions (LBGI) for Basalog compared to Lantus (2.3±3.37 vs 3.4±4.90, p=0.107). CONCLUSION With lesser low glycemic excursions, Basalog may be a feasible alternative basal insulin as compared to Lantus in Type 2 patients with diabetes.